Ultrabooks defining future PCs. IN Gadgets Gallery. - Gomez, Raquel P.
Intel is once again transforming the personal computer to further enrich the web life of consumers.
Keywords: Personal computers; Ultrabooks; Haswell; Ivy Bridge processor